Anti-sliding plate technique for coronal shear fractures of the distal humerus - Song, Zhe (J Orthop Surg Res, 2020)
PURPOSE: The purpose of this study is to discuss the surgical strategy, technical feasibility, and clinical efficacy of coronal shear fractures of the distal humerus using the anti-sliding plate technique. METHODS: Fifty-two patients (35 males and 17 females) were treated with the anti-sliding plate technique in our hospital from January 2012 to January 2017. The average age of the patients was 40.4 years. They were classified according to the Dubberley classification system and treated with the anti-sliding plate technique. The long-term functional scores represented by the Mayo Elbow Performance Index and complications were evaluated. RESULTS: Fractures were classified as follows: 11 type-IA, 5 type-IB, 16 type-IIA, 4 type-IIB, 13 type-IIIA, and 3 type-IIIB according to the Dubberley classification system. All patients were treated with open reduction and internal fixation by the extensile lateral approach and completed a clinical and radiographic follow-up (average, 17.6 months). The average Mayo elbow performance score was 90.6 points, with 36 excellent, 11 good, and 5 fair results. The average range of movement of the elbow joint was 3° (0–15°) for extension and 136° (90–150°) for flexion. CONCLUSIONS: The anti-sliding plate technique follows basic AO principles and neutralizes the shearing force combined with lag screws and/or Kirschner wires after the anatomic reduction of the fracture. It allows for the stable internal fixation of the fracture, which is critical for early mobilization and a good functional outcome. LEVEL OF EVIDENCE: Level IV, Case Series, Treatment Study